Exploring the benefits of olive pomace in poultry nutrition: Effects on egg quality and composition - Schú, Andressa Inês; Righi, Déborah Cristina Barcelos Flores; Marcuzzo, Naila Peil; Souza, Otoniel Félix; Stefanello, Catarina; Speroni, Caroline Sefrin; Cordeiro, Madison Willy Silva; Pozzatti, Marianna; Pinton, Mariana Basso; Wagner, Roger; Morais, Zaloar Cunha; Campagnol, Paulo Cezar Bastianello; et al. (Journal of food composition and analysis, 2025)
Olive oil production has been significantly growing in recent years, especially in Rio Grande do Sul. Olive pomace is produced from olive oil extraction, representing an interesting source of bioactive compounds, vitamin E, and unsaturated fatty acids. However, its incorrect disposal poses a major environmental threat. Several studies have aimed to add olive pomace to animal feed, yielding promising results regarding meat and milk quality and nutritional value. Nonetheless, the effect of adding olive pomace to the diet of laying hens and its impact on eggs remains understudied. Hence, this study aimed to enhance the value of an industrial waste product, olive pomace, in the egg production industry. Thirty-two White Plymouth Rock laying hens and 32 Red Rhodes Island hens were subject to four experimental diets across 16 replicates. The diets included olive pomace residue at the following concentrations: 0 % (C), 2 % (C1), 4 % (C2), and 6 % (C3). The proximate composition and fatty acid profile of the olive pomace, feed, and eggs, lipid oxidation of egg yolks, sensory analysis of eggs, and egg quality (Haugh unit, shell resistance, and yolk color) were analyzed. No significant difference between the Haugh unit and shell resistance was observed between treatments. Minor variations were observed in the other parameters evaluated, such as chemical composition and fatty acid profile. According to the sensory analysis, yolk color was the attribute most significantly influenced by adding olive pomace. The use of olive pomace in feed for laying hens did not negatively affect egg quality and improved egg yolk color. Therefore, olive pomace can be used as a feed pigment to replace commercial pigments aimed at enhancing yolk color, and its inclusion in feed presents an environmentally benign option for disposing of this agro-industrial waste. •Olive pomace inclusion improved the egg yolk color.•The olive pomace did not reduce egg quality parameters.•Olive pomace in chicken feed is an environmentally appropriate solution.•Olive pomace can be used in chicken feed as a pigment.